Implementasi Metode Ummi dalam Program Tahfidzul Qur’an di SD 02 Pucung Lor - Nianti, Vivi Ivan; Adilah, Nuri Afidatul; Prasetyo, Aldi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
The skills of reading and memorizing the Quran are skills that are commonly emphasized in Islamic Education institutions. The methods used also vary. One method that can be implemented is the Ummi method as has been implemented at SD 02 Pucung Lor. This study aims to describe and analyze the implementation of the Ummi method in the Tahfidzul Qur'an program at SD 02 Pucung Lor. This research is a qualitative research with the type of case study. The results showed that the implementation of the Ummi method in the Tahfidzul Qur'an program at SD 02 Pucung Lor was carried out by tahfidz teachers who already had the Ummi method teacher certification. Learning is carried out after teaching and learning activities are completed with different targets for each class. The learning process is carried out in a classical way (all students) and one-on-one (one by one facing the teacher) and combined with games and tones. This makes learning fun. The implication of the implementation of the Ummi method at SD 02 Pucung Lor is to maximize the results of the Quran tahfidzul program.